2003
DOI: 10.1046/j.0022-7722.2003.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and fragmentation of the superficial cortex in the abdominal and pelvic lymph nodes of elderly Japanese

Abstract: Gaps and fragmentation of the superficial lymph node cortex are considered to provide intranodal shunt flow between the afferent and efferent vessels. Using serial sections of 205 nodes obtained from 27 donated cadavers more than 70 years of age, we examined the histological architecture of the abdominal and pelvic nodes in elderly Japanese. Secondary follicles were rare in the specimens. Cortex gaps were, to a greater or lesser degree, found in all nodes. We classified these nodes into three types according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The proportion of the cross‐sectional area of axillary and inguinal lymph nodes occupied by follicular cortex decreased from approximately 10–25% in young adults to about 5% in those >70 years of age; cervical and mesenteric nodes failed to show this decline. In contrast, studies in elderly Japanese cadavers with no history of neoplasia found that superficial lymph nodes from cervical, axillary and inguinal regions generally had better preserved cortical lymphoid tissue than visceral nodes . These authors noted that cortical deficiencies were most apparent in colic, para‐aortic and pelvic lymph nodes.…”
Section: Lymph Node Morphologymentioning
confidence: 93%
See 4 more Smart Citations
“…The proportion of the cross‐sectional area of axillary and inguinal lymph nodes occupied by follicular cortex decreased from approximately 10–25% in young adults to about 5% in those >70 years of age; cervical and mesenteric nodes failed to show this decline. In contrast, studies in elderly Japanese cadavers with no history of neoplasia found that superficial lymph nodes from cervical, axillary and inguinal regions generally had better preserved cortical lymphoid tissue than visceral nodes . These authors noted that cortical deficiencies were most apparent in colic, para‐aortic and pelvic lymph nodes.…”
Section: Lymph Node Morphologymentioning
confidence: 93%
“…There is general agreement that the volume of cortical lymphoid tissue in adult lymph nodes diminishes with senescence . As the cortex shrinks, it may become fragmented into ‘islands’ separated by expanding cortical and medullary sinuses . There is also loss of paracortical tissue, normally populated mainly by T cells, but the interface between B and T lymphocytes tends to be preserved .…”
Section: Lymph Node Morphologymentioning
confidence: 99%
See 3 more Smart Citations